1992
DOI: 10.1021/ma00038a027
|View full text |Cite
|
Sign up to set email alerts
|

Particle beam-induced reactions versus thermal degradation in PMDA-ODA polyimide

Abstract: Chemical reactions induced by heat and particle bombardment at low energy in PMDA-ODA have been studied by XPS and REELS. Different chemical reactions involving the chemical state of oxygen and nitrogen are shown to occur with different products and rates depending on the peculiar way of energy deposition. In particular, thermal treatments proceed mainly by decarbonylation of imidic rings, leaving the ether linkage in the PMDA-ODA unit essentially unaffected. Evidence is found that thermal treatment results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 7 publications
(8 reference statements)
0
21
0
Order By: Relevance
“…Consequently, it might be assumed that there is no indication of ring opening by cleavage of the aromatic structure after plasma treatment. Therefore, due to the stability of etherlike bonds, which is attributed to the high radiation resistance of the ether linkage stabilized by the two contiguous benzene rings [27], it is most likely that the oxygen incorporation occurs into the benzene rings [28]. According to these results, the changes in the chemical structure of PEEK are discussed hereinafter.…”
Section: Surface Chemical Analysismentioning
confidence: 99%
“…Consequently, it might be assumed that there is no indication of ring opening by cleavage of the aromatic structure after plasma treatment. Therefore, due to the stability of etherlike bonds, which is attributed to the high radiation resistance of the ether linkage stabilized by the two contiguous benzene rings [27], it is most likely that the oxygen incorporation occurs into the benzene rings [28]. According to these results, the changes in the chemical structure of PEEK are discussed hereinafter.…”
Section: Surface Chemical Analysismentioning
confidence: 99%
“…Inagaki et al [8] studied PEEK surfaces modified by using remote oxygen plasma and observed that degradation products were formed on the PEEK surface by the oxygen plasma treatment. The formation of new groups on the surface of PEEK after plasma treatment is attributed to the depletion of hydrocarbon in the benzene ring and uptake of oxygen by polymer surface leading to the formation of C-O-C (or C-OH), C=O and O-C=O groups while the stability of the carbonylic component and the ether like bond is due to the high radiation resistance of linkages stabilized by two contiguous benzene rings [14,15].…”
Section: Ray Photoelectron Spectroscopy (Xps) Analysismentioning
confidence: 99%
“…This reaction is not only known from the early stage of PI pyrolysis 37 but also from irradiation with ions in the keV energy regime. 38 …”
Section: ϫ1mentioning
confidence: 99%